2015
DOI: 10.1104/pp.15.00597
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Morphogenesis of the Endoplasmic Reticulum Driven by the Membrane Domain of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase in Plant Cells

Abstract: The enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) has a key regulatory role in the mevalonate pathway for isoprenoid biosynthesis and is composed of an endoplasmic reticulum (ER)-anchoring membrane domain with low sequence similarity among eukaryotic kingdoms and a conserved cytosolic catalytic domain. Organized smooth endoplasmic reticulum (OSER) structures are common formations of hypertrophied tightly packed ER membranes devoted to specific biosynthetic and secretory functions, the biogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 69 publications
(94 reference statements)
6
66
0
Order By: Relevance
“…Another possibility for the lower incorporation rate of mevalonate in certain tissues and not others might be with respect to the channeling of mevalonate during sterol biosynthesis. Such metabolic channels or metabolons (Chappell , Newman and Chappell , Winkel , Ferrero et al ) may restrict substrate accessibility such that mevalonate enters the sterol biosynthetic pathway more readily in leaves but not in stems and roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility for the lower incorporation rate of mevalonate in certain tissues and not others might be with respect to the channeling of mevalonate during sterol biosynthesis. Such metabolic channels or metabolons (Chappell , Newman and Chappell , Winkel , Ferrero et al ) may restrict substrate accessibility such that mevalonate enters the sterol biosynthetic pathway more readily in leaves but not in stems and roots.…”
Section: Discussionmentioning
confidence: 99%
“…Of significance is the responsiveness of plant HMGR to developmental and environmental signals (Choi et al , Stermer et al , Learned , Korth et al ) and its tight regulation at both the transcriptional and posttranscriptional levels (Stermer et al , Nieto et al , Leivar et al ). Recent findings point to dual functionality (catalytic vs non‐catalytic states) for plant HMGR in isoprenoid production and ER biogenesis (Ferrero et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein-protein and lipid-protein interactions, and/or lipid alterations, appear to play important roles in cubic membrane formation. In plants, it has been reported that the membrane domain of the enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase is key for the proliferation of the ER and the formation of organized smooth endoplasmic reticulum (OSER) [157]. Additionally, it has been reported that the concentration of docosapentaenoic acid (DPA, C22:5n-6) in the cubic membrane of mitochondria in starved amoeba Chaos cells is about 1.6-fold higher than in fed cells.…”
Section: Structure and Formation Mechanismmentioning
confidence: 99%
“…Occasionally this membrane expansion has been assessed directly (e.g. by fluorescence microscopy of cells expressing tagged variants of ER-resident proteins or by examination of thin-section electron micrographs (126)(127)(128) ) but more often it is detected less directly as an increase in the expression and/or activity of phospholipid-synthesising enzymesusually CTP:phosphocholine cytidylyltransferase, the rate-limiting enzyme in phosphatidylcholine (PtdCho) synthesis by the Kennedy pathway (23,125,(129)(130)(131) .…”
Section: The Upr and Er Membrane Expansion: Two Faces Of Cell Responsmentioning
confidence: 99%